A Review of Research on Water Jet with Slurry Injection. (2016) - Molitoris, Matúš; Piteľ, Ján; Hošovský, Alexander; Tóthová, Mária; Židek, Kamil
Abstract: Abrasive water jet has been used for more than thirty years. It quickly became one of the core non-conventional technologies for cutting operations of various materials, ranging from soft and easy to cut materials, through ductile metal materials to brittle, hard to cut ceramics and metals. Abrasive water suspension jet (AWSJ) did not gain much popularity in machining industry in the beginning as opposed to abrasive water injection jet, but has found niche applications where its advantages were put to use. In this study a review of recent development in the eld of AWSJ is presented. Micro-machining, as a potential application for AWSJ, is discussed at the beginning, followed by several advances in the AWSJ technology. At the end, typical applications for AWSJ as decommissioning and dismantling of structures or rock drilling are presented.